Calibración de equipo de radiodiagnóstico no fluoroscópico - Rosenthal C., Salomón (Revista Mexicana de Ingenieria Biomedica, 2018)
In this paper we present a series of test protocols for the quality control of diagnostic equipment. For each of these tests we discuss the objectives, we present the detailed procedure to be followed and establish the quality control acceptance criteria. For an X-Ray unit to be considered in optimal operating conditions, ithas to satisfy each one of the testes. The factors under control are the following: beam quality, radiation emission, mA linearity, exposure time, KVp, focal-spot size, light field-X ray beam coincidence, focal-spot-table-top distance and beam waveform.